Synthesis and characterization of copper-loaded hydroxyapatite-alginate microspheres - A. A. Yanovska; S. B. Bolshanina; A. S. Stanislavov; V. N. Kuznetsov; A. B. Mospan; V. Yu. Illiashenko; Yu. V. Rogulsky; Ya. V. Trofimenko; S. N. Danilchenko (Хімія, фізика та технологія поверхні)
Microspheres of hydroxyapatite (HA) in alginate (Alg) shell can be successfully used for controlled release of drugs, growth factors, and antibacterial compounds. Hydroxyapatite is a perfect material for biomaterials production due to its high sorption capacity to metal ions, low solubility in water, high stability to oxidisers and reducers, low cost and biocompatibility. Sodium alginate used for microspheres formation due to its cross-linking capability with divalent cations (Cu2+, Ca2+ etc.). Microspheres  HA/Alg-Cu were obtained by 2 variants of synthesis and showed more rough surface than that of microspheres HA/Alg-Ca what is better for cell proliferation. XRD results show that HA is the main crystalline phase in obtained microspheres. According to the results of adsorption kinetics study, HA has the main contribution in process of Cu2+ ions adsorption. The temperature, increasing the rate of the adsorption process, has negligible effect on the adsorption capacity of HA due to the saturation of energetically heterogeneous active sites on the microspheres surface with Cu2+ ions. Adsorption index of HA/Alg microspheres to Cu2+ ions was calculated to be above 60 mg/g. Adsorption of Cu2+ ions on HA/Alg microspheres has an ion-exchange character. Due to the Cu2+ ions release obtained microspheres showed antibacterial effect on S. aureus and E. coli in concentration 6 mg/mL.